Content and structure of future teachers' aesthetic perception of fine and decorative applied art creations - Liudmyla Lisunova (Vasyl Stefanyk Precarpathian National University, 2017)
The content and structure of future teachers' aesthetic perception of fine and decorativeapplied art creations in the system of professional training are delivered in this article. Thestructural components and stages (phases) of aesthetic perception process are determined, therole of art as the most powerful source of reality in the process of future teachers' aestheticperception of art are revealed. Key words: contents and structure of aesthetic perception, future teachers of art, fineand decorative applied art creations